PERSONALITY : THEORY AND RESEARCH - Cervone, Daniel, author 349402; Pervin, Lawrence A., author 280829 (Hoboken, NJ : Wiley, 2023)
"The 14th edition of Personality: Theory and Research began with sad news: The passing of Professor Lawrence A. Pervin. When Professor Pervin launched this textbook decades ago, he originated the idea that remains its driving concept: to combine, for the benefit of the student, coverage of personality theory, personality research, and clinical case examples. Professor Pervin's name remains on the 15th edition because his intellectual imprint is still felt on every page. This new edition begins with more sad news: The passing of the two major 20th-century personality theorists who were with us at the time of the previous edition: the social-cognitive theorists Albert Bandura (who passed away in July of 2021) and Walter Mischel (who passed away in September of 2018). Bandura's impact is unparalleled. As we note in the main text, in the early decades of the 21st century he was the most highly cited living author not merely in psychology but in the entire social sciences. He also was your present author's graduate school mentor-an incalculably valuable, career-shaping experience for me. Walter Mischel was a legendary researcher, a legendary theorist, a legendary critic of personality psychology's status quo-and, to me, an inspiration and a friend. His undergraduate textbook was my introduction to the field. His freewheeling personality graduate course was a highlight of my grad school years. His openness to collaboration on Advances in Personality Science (2002) and related projects was a great honor. Thanks to Walter, somehow all of it was great fun, too"--